Assessment of Structural and Process Readiness for Postpartum Haemorrhage Care in Uganda and Ghana: A Mixed Methods Study - Tancred, Tara; Weeks, Andrew D; Mubangizi, Vincent; Dei, Emmanuel Nene; Natukunda, Sylvia; Cobb, Chloe; Bates, Imelda; Asamoah- Akuoko, Lucy; Natukunda, Bernard (An International Journal of Obstetrics & Gynaecology, 2024)
Objective: To determine structural and process readiness for postpartum haemorrhage (PPH) care at referral- level facilities in Ghana and Uganda to identify opportunities for strengthening. Design: Mixed- methods cross- sectional study. Setting: Three districts in Ghana and two in Uganda. Population or Sample: Nine hospitals in Ghana and seven in Uganda; all hospitals had theoretical capacity for caesarean section and blood transfusion. Methods: We deployed a modular quantitative health facility assessment to explore structural readiness (drugs, equipment, staff) complemented by in- depth interviews with maternity health service providers to understand process readiness (knowledge, attitudes, and practices as related to World Health Organization [WHO] guidance on PPH care). Main Outcome Measures: Availability of essential structural components needed to support key PPH processes of care. Results: In both countries, there was generally good structural readiness for PPH care. However, key common gaps included inadequate staffing (especially specialist physicians), and unavailability of blood for transfusion. Interviews highlighted particularly good process readiness in the provision of uterotonics, recognising and responding to retained placenta, and repairing tears. However, there were clear gaps in the utilisation of tranexamic acid and uterine balloon tamponade. Conclusions: We have identified good structural and process readiness across both Ghanaian and Ugandan health facilities to support PPH responses. However, some key missed opportunities—to align with current WHO guidance on providing bundles of interventions for PPH care—could be strengthened with minimal investment but promising impact.
Keywords: Caesarean; Facility readiness; Ghana; Postpartum haemorrhage; Transfusion; Uganda